Optical magnetoplasmons in rhombohedral graphite with a three-dimensional Dirac cone structure. (5th March 2015) - Ho, Ching-Hong; Chang, Cheng-Peng; Lin, Ming-Fa
Abstract: Rhombohedral graphite has a three-dimensional Dirac cone structure, differing only perturbatively from the bulk stack of independent graphene layers, so that the three-dimensional integer quantum Hall effect can be well exhibited in this system. In this paper, optical magnetoplasmons are obtained by using the random phase approximation. Such collective excitations do not exist in monolayer graphene but are shown to originate from Landau level mixing due to interlayer Coulomb interaction in the quantum Hall effect regime. The three-dimensional character of rhombohedral graphite is thus demonstrated. The results should be realized in response to a longitudinal external electric field or an incident infrared electromagnetic wave.